Manajemen Risiko dalam Strategi Pemasaran Retail: Studi Kualitatif Usaha Buket Bunga Segar - Lu’lu Jilan Zain; Lutfi Zulkarnain; Pranoto Effendi (GREAT: Jurnal Manajemen dan Bisnis Islam, 2025)
The florist industry has significant growth potential; however, it faces various challenges, including operational, financial, and supply chain risks. This study aims to analyze the implementation of risk management in the fresh flower bouquet business at Ramdan Florist and identify the mitigation strategies employed to ensure business sustainability. The research adopts a qualitative descriptive method, utilizing data collection techniques such as interviews, observations, and documentation. The findings reveal that Ramdan Florist encounters several key risks, including limited fresh flower supply due to weather conditions, fluctuations in raw material prices, and rapid changes in market trends. To address these challenges, Ramdan Florist implements various mitigation strategies, such as establishing partnerships with alternative suppliers, adopting a more efficient inventory management system, and aligning marketing strategies with consumer trends. Additionally, a digital approach through social media is leveraged to enhance competitiveness and expand market reach.